New perspectives on aryl azide noncanonical amino acid use in yeast. Issue 1 (25th October 2018) - Tippmann, Eric M.; Culpepper, Seja; Bunnel, Wade; Appel, Nolan
Abstract : A photochemically chemically active noncanonical amino acid para -azido-l -phenylalanine widely used in biology was found to be metabolized by Saccharomyces cerevisiae . Abstract : A photochemically chemically active noncanonical amino acid para -azido-l -phenylalanine widely used in biology was found to be metabolized by Saccharomyces cerevisiae . Contrary to multiple reports, the azide moiety is not reduced to the corresponding amine. The amino acid's concentration was found to decline somewhat with time which was due, at least in part, to modification of the amino acid side chain. The metabolite was found to be photochemically active and further characterization concluded the azide moiety was still intact. This work also goes onto highlight paramount areas of concern with regards to (photo)chemical compatibility, handling, and fidelity in genetically encoding aryl azide amino acids.